2020
DOI: 10.21203/rs.3.rs-126149/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequency Domain Measurements of Melt Pool Recoil Force Using Modal Analysis

Abstract: Recoil pressure is a critical factor affecting the melt pool dynamics during Laser Powder Bed Fusion (LPBF) processes. Recoil pressure depresses the melt pool, providing layer-to-layer fusion without introducing porosity. If the recoil pressure is too low, the process operates in a conduction mode where layers will not properly fuse, while excessive recoil pressure leads to a keyhole mode, which results in gas porosity. Direct recoil pressure measurements are challenging because it is localized over an area pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Experimental measurements by Cullom et al reported values for the recoil pressure in the range of tens of kPa which were found to be in agreement with the results reported by Yin et al [37,61]. Although, the recoil pressure levels reported in the current work are well beyond values reported in literature they still confirm the predominance of the recoil pressure over other dynamic components.…”
Section: Implementation Of the Analytical Model To Estimate Recoil Pr...supporting
confidence: 91%
See 1 more Smart Citation
“…Experimental measurements by Cullom et al reported values for the recoil pressure in the range of tens of kPa which were found to be in agreement with the results reported by Yin et al [37,61]. Although, the recoil pressure levels reported in the current work are well beyond values reported in literature they still confirm the predominance of the recoil pressure over other dynamic components.…”
Section: Implementation Of the Analytical Model To Estimate Recoil Pr...supporting
confidence: 91%
“…to be smaller in orders of magnitude and may be considered as secondary effects over the fluid motion [37,38].…”
Section: Analytical Model To Determine Recoil Pressure Variationsmentioning
confidence: 99%